School children growth monitoring program in the state of Qatar: Observations from two survey rounds in 2016–17 and 2019–20 - Mohammed H. Al‐Thani (21406742) (2023)
Introduction Growth monitoring surveys provide critical anthropometric data to monitor physical growth and various forms of malnutrition among school age children. In the beginning, growth monitoring programs were introduced to identify the extent of undernutrition among children, which were later considered equally useful in the identification of overweight and obesity among school age children. Observing the shifts in weight categories among school age children provides an important insight to design targeted interventions for improving growth and development of children. Methodology The study used growth monitoring survey data among 5–19‐year school children of two academic years (2016–17 and 2019–20) in Qatar where 2016–17 survey included 186,986 students, whereas 2019–20 survey included 215,279 students. A total of 7514 unique records of students aged 5–14 years available in both survey rounds were included in the final analysis. This study documented shift in BMI‐z‐scores to ascertain the movement of students among obese, overweight, normal, thinness, and severe thinness categories. Python version 3.9.5 was used for data analysis along with a pairwise comparison between each of BMI‐z‐score shift to evaluate the effects of specific shifts in BMI‐z‐score category. Results Overall, the proportion of overweight and obese category of students increased from 44% in 2016–17 to 49.3% in 2019–20 with a decrease in the proportion of students in normal BMI‐z‐score category (from 48.8% to 47.8%) and severe thinness and thinness category (from 7.3% to 3%) between two rounds of growth monitoring survey. Statistically significant shifts in BMI‐z‐score categories were noted for students of different age groups, gender, and nationality. Conclusions Shift from normal BMI‐z‐score to obese and overweight category is a cause of concern and an opportunity to develop appropriate interventions. The significant shift among different categories needs to be investigated further to identify associated reasons to effectively develop interventions. Other Information Published in: Public Health Challenges License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/puh2.52